The capital gains tax: A curse but also a blessing for venture capital investment - Ann-Kristin Achleitner; Carolin Bock; Martin Watzinger (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2011)
This article documents a statistical association between the number and success of venture capital investments and the capital gains tax rate. To do this, we analyze investment data and taxes of 32 countries from 2000 to 2010. In our data, higher capital gains tax rates are associated with fewer firms financed and a lower probability for ventures receiving follow-up funding. However, if the first investment is received when taxes are high, the probability of a firm eventually going public or being acquired increases. We conclude that high tax rates are associated with fewer, but on average more successful companies.
Keywords: G24; H25; H32; 330; capital gains tax; venture capital; investment